2011
DOI: 10.1161/circresaha.110.226902
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics

Abstract: Abstract:The concept of using stem cells for cardiovascular repair holds great potential, but uncertainties in preclinical experiments must be addressed before their therapeutic application. Contemporary proteomic techniques can help to characterize cell preparations more thoroughly and identify some of the potential causes that may lead to a high failure rate in clinical trials. The first part of this review discusses the broader application of proteomics to stem cell research by providing an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…23 However, it must be cautioned that some circulating endothelial progenitor cells assays are relatively nonspecific as proteomics has shown that platelet microparticles can cause the transfer of endothelial characteristics to mononuclear cells. 135 During ACS, it has been identified that there is differential mobilization of each of the 3 phenotypes of monocyte (Table 2), 136 but it has not yet been identified how this influences prognosis.…”
Section: Inflammationmentioning
confidence: 99%
“…23 However, it must be cautioned that some circulating endothelial progenitor cells assays are relatively nonspecific as proteomics has shown that platelet microparticles can cause the transfer of endothelial characteristics to mononuclear cells. 135 During ACS, it has been identified that there is differential mobilization of each of the 3 phenotypes of monocyte (Table 2), 136 but it has not yet been identified how this influences prognosis.…”
Section: Inflammationmentioning
confidence: 99%
“…Different proteomics approaches can be employed as reviewed previously. 111 To minimize falsepositives, it is advisable to search for communalities of protein changes after transfection of the precursor as well as inhibition of the endogenous miRNAs. Using pulsed stable isotope labeling by amino acids in cell culture (pSILAC), newly synthesized proteins can be pulse-labeled with different isotopes of amino acids and readily discerned from preexisting proteins.…”
Section: Proteomics and Metabolomics To Assess Direct And Indirect MImentioning
confidence: 99%
“…114 Generally, studies on APCs, previously referred to as endothelial progenitor cells, have to be interpreted with caution given that these early outgrowth cultures tend to be contaminated with platelets. 111,115,116 …”
Section: Proteomics and Metabolomics To Assess Direct And Indirect MImentioning
confidence: 99%
“…15,16 Unlike late-outgrowth ECs, endothelial progenitor cells do not give rise to ECs. Instead, the definition of endothelial progenitor cell has been obscured by the uptake of platelet microparticles by monocytes/macrophages, 17,18 and the mechanisms for the in vivo improvements observed in preclinical models after endothelial progenitor cell administration remain elusive, with paracrine effects, rather than differentiation, being the most likely explanation. Similarly, the authors in the present study speculate that injected cells secrete paracrine factors that have the potential to modify the endogenous healing process.…”
Section: Circulationmentioning
confidence: 99%